2018
DOI: 10.1186/s12933-018-0755-3
|View full text |Cite
|
Sign up to set email alerts
|

Low muscle quality in Japanese type 2 diabetic patients with visceral fat accumulation

Abstract: BackgroundAlthough obesity-related type 2 diabetes mellitus (T2DM) and sarcopenia in the elderly have been increasing worldwide, the associations among visceral fat accumulation, skeletal muscle indices (mass, strength, and quality) and cardiovascular diseases in T2DM remain poorly investigated.MethodsWe enrolled 183 Japanese T2DM inpatients (126 men, 57 women; mean age 64.7 ± 12.6 years, ± SD). The estimated-visceral fat area (eVFA) and skeletal muscle mass were measured by each device using bioelectrical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 51 publications
(53 reference statements)
3
45
0
1
Order By: Relevance
“…Field MQI used the ratio of grip strength by the BMI (Barbat-Artigas et al, 2012;Choquette et al, 2010;Straight et al, 2013;Studenski et al, 2014). The validity and reliability of the MQI measures (field and laboratory) have been previously reported and the definition of muscle quality adopted in this study is commonly used in large-scale studies because of its convenience (Barbat-Artigas et al, 2012;Barbat-Artigas et al, 2013a;Choquette et al, 2010;Murai et al, 2018;Straight et al, 2013;Studenski et al, 2014).…”
Section: Muscle Qualitymentioning
confidence: 92%
See 1 more Smart Citation
“…Field MQI used the ratio of grip strength by the BMI (Barbat-Artigas et al, 2012;Choquette et al, 2010;Straight et al, 2013;Studenski et al, 2014). The validity and reliability of the MQI measures (field and laboratory) have been previously reported and the definition of muscle quality adopted in this study is commonly used in large-scale studies because of its convenience (Barbat-Artigas et al, 2012;Barbat-Artigas et al, 2013a;Choquette et al, 2010;Murai et al, 2018;Straight et al, 2013;Studenski et al, 2014).…”
Section: Muscle Qualitymentioning
confidence: 92%
“…Laboratory MQI in both cross-sectional studies used the ratio of grip strength to the entire arm muscle in kilograms measured by DXA (Murai et al, 2018). Field MQI used the ratio of grip strength by the BMI (Barbat-Artigas et al, 2012;Choquette et al, 2010;Straight et al, 2013;Studenski et al, 2014).…”
Section: Muscle Qualitymentioning
confidence: 99%
“…PBF was calculated as the total mass of fat divided by total body mass. VFI is a novel and accurate and reliable indicator for assessing body fat stored around important internal organs, which is significantly associated with many health‐related outcomes, such as prehypertension, adipose tissue dysfunction, and type 2 diabetes . Bioimpedance analysis is a measurement technique based on electrophysiological characteristics of the dielectric and conductive properties of human tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that fatness is a mediator of muscular fitness and metabolic syndrome [44] in adolescents and, similarly, Brand et al [45] and Bailey et al [46] found that body fat mediated the relationship between cardiorespiratory fitness and cardiovascular risk factors. Also, it has been shown that patients with T2DM and with visceral fat accumulation have low muscle quality [47]. Although we did not perform measures of muscle quality per se, previous evidence is suggestive that total and regional adiposity is associated with inter-and intramuscular adipose tissue infiltration, which is considered to be an important anatomical correlation of poor muscle quality [48].…”
Section: Discussionmentioning
confidence: 87%